A Retrospective Analysis of the Azerbaijani Economy During 30 Years of Independence - G. Ibadoghlu; I. M. Niftiyev (Проблемы постсоветского пространства, 2022)
Here, we retrospectively describe the Azerbaijani economy since its independence from the Soviet Union in terms of the main macroeconomic indicators that evolved throughout the developmental phases and economic cycles of the country. The study identifies five distinct stages of the Azerbaijani economy, namely a recession (1991–1994), recovery (1995–2003), peak (2004–2006), oil boom (2007–2014), and post-boom (2015–2020). Our analysis mainly utilized the numerical analysis and period-based grouping of the main macroeconomic indicators. Therefore, the recovery period was notable due to rapid reforms, and the economic peak reflected the consequences of the government’s oil-driven economic growth. However, stagnation and the post-boom period hit the Azerbaijani economy with full force, and revealed the harsh reality of oil dependency. In other words, the sustainability of the Azerbaijani economy seems to be below average as the growth of the main macroeconomic indicators are both highly and positively correlated with the oil industry and its many-sided effects. Extractive industries are non-renewable and rapidly exhausted. The commodity prices are highly volatile, and many political regimes of the oil-rich countries improperly manage windfall revenue. The future policy concerns of the Azerbaijani government officials should focus on rechanneling the available economic and institutional resources to address the lagging performance of the non-oil tradable sectors in the future. Otherwise, a wider and deeper recession will be unavoidable.